Anselm: Platonism, language and truth in Proslogion - Baark, Sigurd (Scottish journal of theology, 2010)
When the Proslogion is read from within the context of Anselm's De Veritate it seems that Anselm's project is firmly based on theological premises. Anselm works with a two-fold conception of truth. Truth is first of all a quality inherent in the statement itself. It is the correctness (rectitudo) of the statement. Second, truth is the correspondence with the extra-linguistic reality. This second level of truth is accidental to the statement. What provides the link between extra-linguistic reality and the statement is the Word of God, which is the level of true reference, where original statements correspond to the original will of God in the creation. When Plato asks what true knowledge is in the Theatetus, the final answer seems to be that what is needed is a statement which carries its own truth as a certainty of Being and Unity within itself. However, no such statement is presented in the dialogue. The name of God in the Proslogion is such a statement which carries its own truth as a certainty of Being and Unity within itself, in that on the first level of truth (rectituto) it is impossible to deny. As the statement concerns the Being of God and cannot be denied it necessarily overflows into the second level of truth which is correspondence with extra-linguistic reality. Therefore, this article argues that Anselm develops a statement which fulfils the criterion of true knowledge presented in the Theatetus. He manages to do this from the position of faith, which includes a strict theological rationality.